Early medieval Venice - Berto, Luigi Andrea, author.
1 online resource.
Keywords: "Early Medieval Venice examines the significant changes that Venice underwent between the late-sixth and the early-eleventh centuries. From the periphery of the Byzantine Empire, Venice acquired complete independence and emerged as the major power in the Adriatic Sea. It also avoided absorption by neighbouring rulers, prevented serious destruction by raiders, and achieved a stable state organization, all the while progressively extending its trading activities to most of northern Italy and the eastern Mediterranean. This was not a linear process, but the Venetians obtained and defended these results with great tenacity, creating the foundations for the remarkable developments of the following centuries. This book presents the most relevant themes that characterized Venice during this epoch, including war, violence, and the manner in which 'others' were perceived. It examines how early medieval authors and modern scholars have portrayed this period, and how they were sometimes influenced by their own 'present' in their reconstruction of the past"--